2017
DOI: 10.1016/j.jpeds.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Characteristics of Children with Blood Lead Levels ≥45 μg/dL

Abstract: Although the incidence of lead poisoning has declined in the US, severe cases still occur. Physicians should be especially vigilant in certain at-risk populations including children who eat paint chips or soil, spend time outside the US (particularly in Pakistan), use imported products, or have developmental delays or sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…In the present day, Black children continue to have the highest average BLLs in the US compared to either non-Hispanic White or Hispanic children [38]. Black race remains a strong independent predictor of more blood Pb throughout childhood [39][40][41][42][43][44][45][46]. Geospatial analyses have demonstrated that increasing concentrations of exposure to Pb from the air, soil, water, or industrial releases are associated with early childhood BLLs [47][48][49][50][51][52][53][54], while an increasing percent Black population is a strong predictor for higher blood Pb among young children in US cities, states, and nationwide across the US [32][33][34]39,40,53,[55][56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…In the present day, Black children continue to have the highest average BLLs in the US compared to either non-Hispanic White or Hispanic children [38]. Black race remains a strong independent predictor of more blood Pb throughout childhood [39][40][41][42][43][44][45][46]. Geospatial analyses have demonstrated that increasing concentrations of exposure to Pb from the air, soil, water, or industrial releases are associated with early childhood BLLs [47][48][49][50][51][52][53][54], while an increasing percent Black population is a strong predictor for higher blood Pb among young children in US cities, states, and nationwide across the US [32][33][34]39,40,53,[55][56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…Mitra et al reported that, in Bangladesh, among 345 children (6 months–12 years old), 39% were detected with BLLs ≥ 10 µg/dL [ 6 ]. Finally, Pakistan is also characterized as a country of elevated risk for lead exposure [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While typical environmental sources predominate as the cause of lead poisoning, cultural factors are also important. Besides lead-containing paint, various sources of lead were identified for children with BLL ≥ 45 μg/dL in New York City: imported spices, cosmetics, as well as traditional folk medicines [ 8 ]. A detailed history about the usage of traditional folk medicine is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely elevated BLLs (BLLs ≥70 μg/dL) now occur rarely in children [ 8 ]. We report three cases of severe childhood lead poisoning from folk medications specifically prescribed for treating rhinitis.…”
Section: Introductionmentioning
confidence: 99%